Insights on the Russian HCV care cascade: minimal HCV treatment for HIV/HCV co-infected PWID in St. Petersburg. Issue 1 (December 2016) - Tsui, Judith; Ko, Stephen; Krupitsky, Evgeny; Lioznov, Dmitry; Chaisson, Christine; Gnatienko, Natalia; Samet, Jeffrey
Abstract Background The human immunodeficiency virus (HIV) epidemic in Russia, driven by injection drug use, has seen a steady rise in the past two decades. Hepatitis C virus (HCV) infection is highly prevalent in people who inject drugs (PWID). The study aimed to describe the current frequency of HCV testing and treatment among HIV-infected PWID in St. Petersburg, Russia. Methods This study examined baseline data from the "Linking Infectious and Narcology Care" (LINC) and "Russia Alcohol Research Collaboration on HIV/AIDS" (Russia ARCH) studies. Participants included in this analysis were HIV-infected with a history of injection drug use. Descriptive statistics were performed to assess frequency of HCV testing and treatment. Results Participants (n = 349 [LINC], 207 [Russia ARCH]) had a mean age of 33.8 years (IQR: 31–37) in LINC and 33.0 (IQR: 30–36) in Russia ARCH; 26.6 % (LINC) and 29.0 % (Russia ARCH) were female; 100 % were Caucasian. Nearly all participants had been tested for HCV (98.9 % in LINC, 97.1 % in Russia ARCH). Almost all reported being diagnosed HCV positive (98.9 % in LINC, 97.1 % in Russia ARCH). Only 2.3 % of LINC and 5.0 % of Russia ARCH participants reported ever receiving HCV treatment. Conclusions Among these cohorts of HIV-infected PWID in St. Petersburg, Russia, as of 2015 nearly all reported being tested for HCV and testing positive, while only 3.3 % received any HCV treatment. In this new era of effective HCV pharmacotherapy, an enormous chasm in the HCV treatment cascade in Russia exists providing substantial opportunities for curing HCV in HIV-infected Russians with a history of injection drug use. Trial registration The studies described were registered with ClinicalTrials.gov through the National Institutes of Health: Linking Infectious and Narcology Care in Russia (LINC) -NCT01612455, registered 1 June 2012, first participant enrolled 3 July 2012; Alcohol's Impact on Inflammatory Markers in HIV Disease - Russia ARCH Cohort -NCT01614626, registered 25 May 2012, first participant enrolled 15 November 2012.